Root Associated Bacillus sp. Improves Growth, Yield and Zinc Translocation for Basmati Rice (Oryza sativa) Varieties - Shakeel, Muhammad; Rais, Afroz; Hassan, Muhammad Nadeem; Hafeez, Fauzia Yusuf (Frontiers in Microbiology, 2015)
Plant associated rhizobacteria prevailing in different agro-ecosystems exhibit multiple traits which could be utilized in various aspect of sustainable agriculture. Two hundred thirty four isolates were obtained from the roots of basmati-385 and basmati super rice varieties growing in clay loam and saline soil at different locations of Punjab (Pakistan). Out of 234 isolates, 27 were able to solubilize zinc (Zn) from different Zn ores like zinc phosphate [Zn3 (PO4)2], zinc carbonate (ZnCO3) and zinc oxide (ZnO). The strain SH-10 with maximum Zn solubilization zone of 24 mm on Zn3 (PO4)2 ore and strain SH-17 with maximum Zn solubilization zone of 14-15 mm on ZnO and ZnCO3 ores were selected for further studies. These two strains solubilized phosphorous (P) and potassium (K) in vitro with a solubilization zone of 38-46 mm and 47-55 mm respectively. The strains also suppressed economically important rice pathogens Pyricularia oryzae and Fusarium moniliforme by 22-29 % and produced various biocontrol determinants in vitro. The strains enhanced Zn translocation towards grains and increased yield of basmati-385 and super basmati rice varieties by 22-49 % and 18-47 % respectively. The Zn solubilizing strains were identified as Bacillus sp and Bacillus cereus by 16S rRNA gene analysis.